Midwives' and obstetricians' level of knowledge of appropriate gestational weight gain recommendations for pregnancy: A systematic review. Issue 4 (6th April 2020) - Callaghan, Shauna; O'Brien, Eileen; Coughlan, Barbara; McAuliffe, Fionnuala M.
Abstract: Background: Excessive gestational weight gain (GWG) is a modifiable risk factor associated with maternal and infant health, and pregnancy outcomes. However, several factors influence the provision of health promotion advice including professional knowledge. This review aims to summarize published evidence relating to midwives' and obstetricians' knowledge of GWG guidelines. Methods: Electronic database searches were carried out using EMBASE, CINAHL, PubMed, Web of Science, and Cochrane Database. English‐language studies and quantitative results were included. Identified studies were screened by two authors independently. Disagreements were discussed with a third reviewer. A review protocol was submitted for registration with PROSPERO in May 2019. Results: From 10 960 records identified in preliminary searches, 12 studies reporting on 2652 midwives and obstetricians collectively were included. All studies were conducted in high‐income countries. Synthesis of data was difficult as guidelines and methods for assessing knowledge varied. Midwives were mainly reported as the leading participant, with limited data available on obstetrician knowledge. Both groups demonstrated insufficient knowledge of GWG guidelines. Self‐reported knowledge was significantly higher than those assessed by direct knowledge. Conclusions: This review highlights a substantial gap in health care professionals' knowledge of GWG guideline content which needs to be addressed. Differences between professionals' direct knowledge and self‐reported knowledge are important for clinical practice as it may inhibit the provision of evidence‐based advice. It is important to accurately assess knowledge in this area to develop further training for midwives and obstetricians to improve health promotion during pregnancy.